Analisis Pengaruh Pengangguran Dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia Di Kabupaten Minahasa Selatan Tahun 2012-2022 - Kennedy Alfian Mokalu; Een Novritha Walewangko; Hanly F. Dj. Siwu (PT. Hasba Edukasi Mandiri, 2025)
Regions can develop if natural and human resources are able to manage them properly. Human development is a process of developing a choice for people to freely choose a prosperous, decent, and valuable life. If human development is successfully carried out, people can experience a healthy and knowledgeable life, and can access useful resources for a decent life. The goal is to know how the unemployment rate and economic growth affect the human development index in South Minahasa Regency. The type of research used by the author is the type of quantitative descriptive research, and the type of data used is the secondary data obtained from BPS South Minahasa. In this study the Multiple Regression analysis model was used. The results of this study showed that the unemployment rate had a negative and significant effect on the human development index, economic growth had a negative effect and was insignificant on the human development index. Both simultaneously negatively affect the human development index.